Managing crime and the fear of crime at railway stations––a case study in South Wales (UK) - Cozens, Paul; Neale, R.; Whitaker, J.; Hillier, D. (2003)
Rail users consistently perceive their risks from crime to be significantly higher than official statistics suggest, discouraging many from using rail transport. The aims of the paper include a discussion of Crime Prevention Through Environmental Design (CPTED) and current policy initiatives for reducing crime and the fear of crime on the railways. This exploratory study focuses on adult passengers' perceptions of crime and nuisance as they relate to the management, design and maintenance of railway stations and their immediate access routes. The study innovatively utilises interactive virtual reality (VR) scenes of ‘representative' stations as the environmental stimulus and concludes that such an approach provides an analytical and pragmatic framework for managers of railway stations that are unlikely to receive Secure Station accreditation.